Learning Outcomes in Thailand : What Can We Learn from International Assessments? - World Bank (World Bank, 2012)
Education quality is crucial to Thailand's future economic success. While lower-income countries in East Asia are experiencing a bulge in their youth population, Thailand's youth labor force is expected to decline by 10 percent over the next decade. As a result, the labor-intensive comparative advantage that contributed significantly to Thailand's past economic performance will diminish. This means that it is essential for Thailand to develop the human capital of its declining young work force to ensure the country's future competitiveness and economic growth. Education is a significant component of human capital development, the economic benefits of which are firmly established in the policy literature to have a positive effect on economic growth. However, the success or failure of education in terms of increasing productivity and growth depends crucially on its quality. Thailand has participated in two international student assessments to measure the quality of education: Organization for Economic Co-operation and Development (OECD's) Program for International Student Assessment (PISA) and the IEA's Trends in Mathematics and Science Study (TIMSS). This study also supports policy dialogue on improving accountability mechanisms for publically funded private schools. The above findings reveal that public schools outperform private schools even though private schools receive public funding. The implication is that the accountability mechanism for private schools that receive public funding needs to be improved in order to ensure that private schools are providing high quality services. There are several international examples of strong accountability mechanisms for publically funded private schools. One example is the voucher scheme used in the Netherlands. This provides schools with equal funding per student with which schools have considerable freedom on how to use this funding; however, they must meet specific performance requirements.